Review of ultra-dense networks integration with device to device (D2D) communication / Muhammad Firdaus Hashim and Nur Idora Abdul Razak - Hashim, Muhammad Firdaus; Abdul Razak, Nur Idora (UiTM Press, 2018)
The current network architecture scene can be a challenge due to the increasing number of user equipment and its diversity. Furthermore, the demand for greater data rates and lower latency by the users are increasing. Deployment of the Ultra Dense Networks (UDN) described is to support future wireless network and meet user demands in future wireless networks. Combined with other technologies such as Device to Device (D2D) communication, it will provide benefit to the wireless communication. In this paper, challenges in existing research efforts are analyzed and future avenues for research is presented. Apart from that, this paper considers the features of the D2D and UDN to collaborate later. Generally, by deployment of large small cells, factors such as the traffic offloading, idle mode capability, power consumption, and energy efficiency should be considered. Basically, from the potential challenges that have been identified, it is obvious that the integration between D2D and UDN is a key enabler for potential solution. Finally, the research gaps for research between integration of UDN and D2D can be identified with challenges and open problems that have been presented.